Usage of Different Spectral Bands in Agricultural Environmental Protection - Burai, Péter; Pechmann, Ildikó (Acta Agraria Debreceniensis, 2004)
Hyper and multispectral imaging systems are widely used in agricultural and environmental protection. Remote sensing techniques are suitable for evaluating environmental protection hazarsd, as well as for agriculture resource exploration. In our research we compared aerial hyper and multispectral images, as well as multispectral digital camera images with the background data from the test site. Hyperspectral records were obtained using a new 80-channeled aerial spectrometer (Digital Airborne Imaging Spectrometer /DAIS 7915/. We have chosen two farms where intensive crop cultivation takes place, as test sites, so soil degradation and spreading of weeds can be intensive as a result of land use and irrigation. We took additional images of air and ground with a TETRACAM ADC wide band multispectral camera, which can sense blue, green and near infrared bands. We had detailed GIS database about the test site. Weed and vegetation map of the area in the spring and the summer was made in 2002. For soil salt content analysis, we gathered detailed data frome an 80x100 m area. When analyzing the images, we evaluated image reliability, and the connection between the bands and the soil type, pH and salt content, and weed mapping. In the case of hyperspectral images, our aim was to choose and analyze the appropriate band combinations. With a TETRACAM ADC camera, we made images at different times, and we calculated canopy, NDVI and SAVI indexes. Using the background data mentioned above, the aim of our study was to develop a spectral library, which can be used to analyze the environmental effects of agricultural land use.